2012
DOI: 10.1007/s00256-012-1383-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of non-mass-like abnormal MR signal intensity with pathological findings surrounding pediatric osteosarcoma and Ewing’s sarcoma

Abstract: MR imaging is helpful in identifying the nature of abnormal signal areas surrounding bone sarcomas that are more likely to be tumor-free, particularly when the signal in the soft tissues surrounding the tumor is feathery and edema-like in appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Masrouha et al evaluated the imaging appearance of these areas and found that when a "feathery pattern" was identified in the adjacent muscle or soft tissues, only normal tissue, edema, or fibrosis remained; however, when a "bulky" appearance was present, tumor was identified in >70% of the cases. 80 Even so, DEMRI is accurate in detecting macroscopic tumor invasion to within 5 mm, but microscopic tumor can extend 3 cm beyond the macroscopic margin. 77 The ultimate criterion for determining whether there has been a favorable response of the osteosarcoma to preoperative chemotherapy is determined by the histopathologic analysis.…”
Section: Mrimentioning
confidence: 99%
“…Masrouha et al evaluated the imaging appearance of these areas and found that when a "feathery pattern" was identified in the adjacent muscle or soft tissues, only normal tissue, edema, or fibrosis remained; however, when a "bulky" appearance was present, tumor was identified in >70% of the cases. 80 Even so, DEMRI is accurate in detecting macroscopic tumor invasion to within 5 mm, but microscopic tumor can extend 3 cm beyond the macroscopic margin. 77 The ultimate criterion for determining whether there has been a favorable response of the osteosarcoma to preoperative chemotherapy is determined by the histopathologic analysis.…”
Section: Mrimentioning
confidence: 99%
“…However, we know that there may be tumor cells in those areas. Masrouha et al 12 reported on 30 cases (27 osteosarcoma and 3 Ewing sarcoma) in which they found that 17.4% of these areas were positive for tumor (viable or necrotic). That is why we included all signal abnormalities in the MRI analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cañadell [9] considered the indications for epiphyseal distraction should include the following: 1) the tumor should be situated in the metaphyseal region; 2) the physeal cartilage should be open; and 3) the tumor should not transgress the physis and should be confirmed by radiography, arteriography, CT or MRI preoperatively and histological examination intraoperatively. At present, MRI is considered to be superior to X-ray and CT in determining the invasive range of malignant tumors of the limbs [16,17]. …”
Section: Discussionmentioning
confidence: 99%